Basic Concepts of Islamic Religious Education Based on Local Wisdom - Abdul Muthalib; Muh. Fuad Nisar; Muhammad Tang (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This research aims to examine the implementation of local wisdom in the Islamic Religious Education (PAI) curriculum and its impact on the understanding and character development of students at UPT SMP PGRI Uluway, Tana Toraja Regency. This study employs a qualitative approach with a case study method, utilizing interviews, observation, and documentation. The results of the study indicate that the internalization of local wisdom, in the form of cultural principles such as mutual cooperation (gotong royong), deliberation (musyawarah), courtesy, and respect for parents, has successfully formulated PAI learning that is more contextual and relevant to the lives of students. These findings are reinforced by various educational theories such as constructivism, humanistic education, contextual teaching and learning (CTL), multiple intelligences, social learning, and character education. The implementation of local wisdom in PAI has proven to enhance religious understanding, strengthen religious character, and foster a sense of love for local culture. Education based on local wisdom not only shapes students' character to be religious, tolerant, and cultured, but also makes the learning process more engaging and meaningful. This research recommends strengthening the local wisdom-based curriculum to realize a holistic, contextual, and grounded education.